The role of perceived fairness, trust, and motivation on tax compliance - Fajriana, Nadia; Saraswati, Erwin; Nurkholis; Rusydi, Mohamad Khoiru (Asian Economic and Financial Review, 2025)
This article aims to analyze the influence of perceptions of procedural, distributive, and retributive fairness, cognitive-based trust, and motivation based on a commitment to voluntary compliance of small and medium enterprise (SME) taxpayers in Surabaya, East Java, Indonesia. The theoretical basis of this study is the theory of motivation and the Slippery Slope Structure. This article uses convenience sampling and a survey approach by distributing questionnaires with digital instruments, and the total number of responses from SME taxpayers is 117. Concrete evidence from the analysis shows that perceptions of fairness (distributive and retributive) and trust (cognitive) increase voluntary tax compliance of SME taxpayers. Motivation (commitment) plays an important role in mediating the perception of (procedural) fairness because the perception of procedural fairness is related to the taxation system: calculating, paying, and reporting, and including if there are things that do not comply with applicable regulations (being inspected and punished), so taxpayers need to convince themselves of their obligations as taxpayers and believe that the system is fair. This study provides a framework for analyzing tax compliance models, which consider perceptions of fairness, taxpayer trust in tax authorities, and commitment to play a major role in voluntary tax compliance, especially among SME taxpayers.